XBP1- IGFBP3 Signaling Pathway Promotes NSCLC Invasion and Metastasis - Luo, Qingxi; Shi, Wenwen; Dou, Bo; Wang, Jun; Peng, Wei; Liu, Xianyu; Zhao, Deze; Tang, Faqing; Wu, Yingfang; Li, Xizhe; Li, Jiajia; Wen, Siqi; et al. (Frontiers in Oncology, 2021)
Lung cancer is the most frequently diagnosed cancer and the main cause of cancer death in the world. X-box binding protein 1 (XBP1), which is an important transcription factor involved in regulating the unfolded protein response (UPR) during endoplasmic reticulum (ER) stress, might act as a potent oncogenic protein in the processes of tumorigenesis, tumor proliferation and metastasis in various cancers. However, the clinical significance and pathological role of XBP1 in non-small cell lung cancer (NSCLC) remains unknown. In this study, we investigated the expression of XBP1s protein in the 104 NSCLC tumor tissues and matched adjacent normal lung tissues (ANLT) by Immunohistochemical (IHC), and we found overexpressed XBP1s protein was associated with NSCLC TNM stages, lymph node metastasis and poor prognosis. The further gain-and loss-of-function experiments indicated overexpression of XBP1s protein promoted cell invasion, migration and metastasis both in vitro and in vivo. Further study showed XBP1s protein could upregulate insulin-like growth factor binding protein-3 (IGFBP3) expression, and regulated NSCLC cells invasion and metastasis by regulating IGFBP3. Taken together, XBP1s protein is markedly overexpressed in NSCLC and serves as an oncogene that play a critical role in NSCLC tumorigenesis and development. Importantly, XBP1s protein might not only be a potential biomarker for metastasis and prognosis but also a potential therapeutic target in NSCLC.